HUBUNGAN MOTIVASI DENGAN SIKAP DALAM PENGGUNAAN ALAT PELINDUNG DIRI PADA PERAWAT - Evi Fitriani; Sri Sudewi Pratiwi Sitio; Evalina Manurung (Jurnal Penelitian Kesmasy, 2019)
The hospitals can be a place where various kinds of microorganisms spread. To prevent such situation, there needs to be an effort to control infection effectively in hospitals, one of the preventation of contamination between nurses and patient is to use personal protective equipment (PPE) every time a treatment conducted. The method of this research is decriptive correlation with cross-sectional approach, which objective is to see correlation between the two variables, namely motivation, as the independent variable, and behaviour, as the dependent variable. The result of is research variable knowledge with pvalue = 0,030, variable graduated with pvalue = 0,395, variable long-time employment with pvalue = 0,022, variable jobholders with pvalue = 0,179, variable policy with pvalue = 0,000, variable supervision with pvalue = 0,000, variable attitude with pvalue = 0,005. As the conclusion from chi-square test result, it was found out that the use of personal protective equipment has correlation with motivation with nurse’s attitude in doing treatment, and the use of personal protective equipment has to be maintained dan become one of the regular activity for nurses in doing treatment. It is suggested to profesional health care in hospital to pay more attention to the nurses’ performance in order to increase the quality of health service to the community, and hospitals should increase the program for supervision, policy, and provision of the use of PPE on nurses to increase the quality of services in hospitals, nurses should always use personal protective equipment in every treatment.